Information and communication technologies management in turbulent business environments - Koh, S. C. L. (S. C. Lenny); Maguire, Stuart, 1951- (Hershey, PA : Information Science Reference, 2009)
"This book aims to inform today's business managers the important ICT strategy in changing business environments, techniques for effective ICT development, and ICT challenges for the future"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Information technology -- Management; Strategic planning